Cognitive Science and Literature. A Cognitive Analysis of the Metaphoric Processes in Shalimar the Clown by Salman Rushdie - Resta, Donatella (Cognitive philology, 2009)
Is it possible to build a bridge between cognitive science and literary production? Cognitive scientists focus on processes and mechanisms of our mind, which influence literary production in both oral and written language, and they highlight a fundamental role to the cultural elements surrounding linguistic and literary phenomena as well. An analysis proposal of the linguistic choices and themes of Rushdie’s novel Shalimar the Clown (2005), with a particular attention towards different levels of metaphorisation, could be a first little step for validating a study across these fields. The starting point of cognitive approach to literature will be the thesis of the cognitive scientist Turner, The Literary Mind (1996), who engages in a detailed examination of the basic principles of the mind emerging from language. The basic aim is to look at the cognitive apparatus lying behind a particular literary production and to test the cognitive approach to literature also in the field of postcolonial literary production. Indeed, the peculiarity of this area of studies seems to match successfully with the frameworks ranging over cognitive science and literary studies.